2018
DOI: 10.1186/s12913-018-3010-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing government insurance scheme beneficiary acceptance of the gatekeeper policy: a cross-sectional study in Wuhan, China

Abstract: BackgroundGatekeeper policy, requiring a patient to visit a primary care provider first, and the patient needs to get his or her primary care provider’s referral before seeing a specialist or going to a hospital, has been implemented in China for about ten years, and it is necessary to assess the patients’ acceptance of gatekeeper policy and to explore the factors influencing patients’ acceptance.MethodsA cross-sectional study with 1162 respondents was conducted between July and September 2015 at four communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
6
1
Order By: Relevance
“…The results showed that only 11.7% patients recognized the community first visit policy ("completely recognize" and "partly recognize" were regarded as recognize), and the majority of patients were not. This finding was much lower than previous studies conducted in Shenzhen (72.03%), Wuhan (43.06%), Nanjing (59.5%), China (37,50,51). Compared with previous studies, there are two major reasons for this difference: First, there is a correlation between understanding of the policy and recognition of the policy for patients.…”
Section: Discussioncontrasting
confidence: 71%
“…The results showed that only 11.7% patients recognized the community first visit policy ("completely recognize" and "partly recognize" were regarded as recognize), and the majority of patients were not. This finding was much lower than previous studies conducted in Shenzhen (72.03%), Wuhan (43.06%), Nanjing (59.5%), China (37,50,51). Compared with previous studies, there are two major reasons for this difference: First, there is a correlation between understanding of the policy and recognition of the policy for patients.…”
Section: Discussioncontrasting
confidence: 71%
“…However, there were only two dimensions, including medical service coverage and satisfaction of the drug list, had a significant impact on acceptance. The previous research which used a EUROPEP scale showed that medical care and organization of care were two dimensions influencing patients’ acceptance of gatekeeper policy in Wuhan, China [23]. Despite differences in survey tools, the conclusion in the medical care coverage had similarity.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire was designed by our team based on a literature study and expert opinions [16, 18, 20, 23]. The questionnaire covered: the demographic and socioeconomic characteristics, including gender, age, marital status, educational level, income level, health status, the proportion of health expenditure in total family spending, and chronic conditions.…”
Section: Methodsmentioning
confidence: 99%
“…However, the current long-term care services for the disabled elderly are not covered by the basic medical insurance in China (42). The disabled elderly may be reimbursed for some medical expenses through inpatient treatment of other diseases (43). Although at this stage the disabled elderly still mainly rely on the help of spouses and children to provide care, but in the future, with the further increase of disabled elderly, and the family size continues to decrease, the nursing care provided by children and families is becoming more and more inadequate, and the demand for nursing care services provided by professional institutions or other social organizations will be greater (25,44).…”
Section: Discussionmentioning
confidence: 99%